Macro and micro-nutrients of Azolla pinnata as a soilless growth media - Shamsudin, Rosnah; Azhari, Nor A. A.; Kasim, Susilawati; Rahmat, Muhammad A. S. (College of Agriculture, University of Basrah, 2021)
Azolla pinnata is a small floating fern which widely occurs in certain regions such as Southeast Asia. Azolla is utilized in the new plant research on the currently existing products for soilless growth media. Soilless growth media are an alternative component to replace soil for cultivation uses. In urbanization scenario nowadays, most of the flatten open-area soil is used for development, affecting the soil supply for plants. To introduce a new component such as the soilless growth media, it must have the same or more nutrients than soil or other existing soilless growth media. A study found that Azolla is used as a soilless growth media in the nursery for olive trees cultivation. According to the study, the nutrients obtained from Azolla are sufficient to replace soil as a growth media. In this experiment, the Single Dry Ashing, and Kjeldahl and Dummas methods were used to evaluate and compare both macro and micronutrients of Azolla to Midorie Pafcal and Jiffy-7 pallets. Based on the results, the values were 0.94 % (N), 4352.00 ppm (P), and 563.13 ppm (K); compared to 1.35% (N), 377.13 ppm (P), 1512.33 ppm (K); and 0% (N), 563.13 ppm (P), 1343.67 ppm (K), respectively. The results also showed the values of Copper (Cu), Iron (Fe), and Zinc (Zn) for Azolla, Midorie Pafcal and Jiffy-7 samples were 15.33 ppm (Cu), 2579.67 ppm (Fe), 93.63 ppm (Zn); 7.53 ppm (Cu), 9988.33 ppm (Fe), 26.77 ppm (Zn); and 13.01 ppm (Cu), 1150.30 (Fe), 12.40 ppm (Zn), respectively. In conclusion, Azolla pinnata is capable of providing the nutrients required for a plant, making it suitable as a soilless growth media for all plants.